2009
DOI: 10.1021/ja9054542
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Diketopiperazine and Oxazolone Structures for HA b2+ Ion

Abstract: Peptide fragmentation can lead to an oxazolone or diketopiperazine b2+ ion structure. IRMPD spectroscopy combined with computational modeling and gas-phase H/D exchange was used to study the structure of the b2+ ion from protonated HAAAA. The experimental spectrum of the b2+ ion matches both the experimental spectrum for the protonated cyclic dipeptide HA (a commercial diketopiperazine) and the theoretical spectrum for a diketopiperazine protonated at the imidazole pi nitrogen. A characteristic band at 1875 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 27 publications
9
131
0
Order By: Relevance
“…Comparison with IR absorption determined using quantum chemical calculation shows that this band can be assigned to the oxazolone C = O stretching [22]. In the case of small b n (n=2) ions, it was found that two strong IRMPD bands in the 1600-1800 cm -1 spectral range constitute IR signatures of diketopiperazine structures [18,19,24]. For larger b n (n ≥4) ions, formation of macrocyclic structures predicted by theory has been confirmed by IR spectroscopy [12,17,25].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Comparison with IR absorption determined using quantum chemical calculation shows that this band can be assigned to the oxazolone C = O stretching [22]. In the case of small b n (n=2) ions, it was found that two strong IRMPD bands in the 1600-1800 cm -1 spectral range constitute IR signatures of diketopiperazine structures [18,19,24]. For larger b n (n ≥4) ions, formation of macrocyclic structures predicted by theory has been confirmed by IR spectroscopy [12,17,25].…”
mentioning
confidence: 68%
“…Most of the attention concerning peptide fragments has been devoted to b n ions [12,[17][18][19][20][21][22][23][24][25]. Nonetheless, a n CID fragments [26][27][28] as well as c n fragment ions [29] generated via electron capture dissociation have also been investigated by IR spectroscopy.…”
mentioning
confidence: 99%
“…IRMPD action spectra were acquired at the CLIO Free Electron Laser Facility (Orsay, France) as described previously [26]. Briefly, peptides were fragmented in a modified Bruker Esquire 3000ϩ ion trap mass spectrometer by using CID.…”
Section: Methodsmentioning
confidence: 99%
“…Gaskell and coworkers used IM-MS to identify both oxazolone and macrocyclic structures for the b 5 ion from YAGFL-NH 2 , while Clemmer and coworkers used a similar approach to identify linear and macrocyclic structures for the a 4 and b 4 fragment ions from leucine enkephalin [21,22]. Variable wavelength action IRMPD spectroscopy has been recently employed by several research groups for the study of gas-phase ions [23][24][25][26] and has also been the subject of two recent, extensive reviews [27,28]. Action IRMPD spectroscopy is ideal for structural characterization of ions, as the IR spectra generated depict the vibrational modes of selected ions, which can be directly correlated to structural features.…”
mentioning
confidence: 99%
“…Paizs and Suhai [1] have pointed out that such a cyclization involves a trans-cis isomerization of the first amide bond that is not being broken and that such an isomerization has a significant energy barrier. However, there are a number of cases [26][27][28][29][30] where diketopiperazine formation has been observed. These involve systems where a side-chain group, such as in His and Arg, acts as a catalyst for the isomerization.…”
Section: Introductionmentioning
confidence: 99%